We Need to Talk About Resilience - William E. Donald; Michael Healy (GiLE Journal of Skills Development)
This essay offers a pragmatic and holistic perspective of resilience to assist careers and employability professionals in supporting university students and graduates. It examines the evolution of employability models from skills-based to capital-based frameworks, emphasising resilience as a key component of psychological capital. Drawing on the Employability Capital Growth Model (ECGM) and sustainable career theory, the essay critiques simplistic views of resilience grounded in positive psychology, advocating for a more nuanced understanding that considers personal, contextual, and temporal dimensions. Drawing parallels with physical strength-building through weight training, it underscores the importance of progressive challenges, mental fortitude, support systems, consistency, and recovery in developing resilience. These factors provide a practical framework for guiding university students and graduates toward sustainable careers, with an emphasis on health, well-being, and long-term productivity. Resilience, the essay argues, is not about unyielding strength but adaptability and recovery, accounting for external factors and systemic barriers. By integrating principles from weight training into career guidance, careers and employability professionals can offer a balanced view of resilience, equipping students and graduates to navigate contemporary career challenges. This approach bridges career development and employability theories, providing new insights for practice and research in higher education and beyond.